Mathur v. Ontario: Grounds for Optimism about the Recognition of a Constitutional Right to a Stable Climate System in Canada? - Wood, Stepan (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
In January 2024, the Court of Appeal for Ontario heard an appeal from a lower court’s dismissal of the first Canadian children’s climate case to be decided on the merits. Mathur v. Ontario alleges that Ontario’s climate change legislation, target and plan violate young people’s rights under sections 7 and 15 of the Canadian Charter of Rights and Freedoms by committing the province to dangerously high levels of greenhouse gas (GHG) emissions. This article argues that there are good grounds to allow the appeal. Some favourable findings will likely be upheld, including the court’s acceptance of climate change science, the global carbon budget, global GHG targets, the inadequacy of Ontario’s new target, the disproportionate impacts of climate change on youth and Indigenous peoples, its rejection of a de minimis defence, and its conclusion that the case as a whole is justiciable. There are, however, grounds to reverse the court’s holdings that Ontario’s share of global GHG emission reductions is not justiciable, the alleged harm is not the result of the impugned state action, the claimed right is positive rather than negative, a positive right is not warranted in this case, any deprivation of section 7 rights accords with principles of fundamental justice, and the impugned state action does not constitute age discrimination. The article also addresses some issues left unresolved by the lower court that may prove important on appeal. Whatever happens, the case will set a key precedent for Canadian environmental rights litigation.